Música como estrategia didáctica para el desarrollo del lenguaje en niños de educación inicial I - Lamilla Caicedo, Helen Guisella (2024)
Didactic music is considered a learning enhancer in children's initial education, which allows the strengthening of knowledge. As the years go by and technology advances, the use of this type of didactic strategies has disappeared. losing, presenting problems such as the limited use of didactic music for the development of language in children, which is why this research is carried out with the main objective of developing language in children in early education through the use of didactic music as a strategy during the learning period. In the methodology, the type of descriptive and explanatory research is applied, which allows the collection and obtaining of information based on bibliography, which allows us to understand the topic of study. The approach used was mixed because it allows integration. of the methods in a single study resulting in the most relevant obtaining of variables such as didactic music and language development, where a sampling of 59 people was demonstrated, including 29 children, 29 parents and a teacher. For this, the survey and observation sheet will be used as techniques, resulting in the feasibility of using music as a teaching strategy, increasing language development. Thus, music as a teaching strategy is an indispensable element in the teaching-learning process of students to enhance their abilities and skills in their school and social environment and at the same time develop their linguistic skills for the literacy process in subsequent studies.